The Catalytic Behaviour of Rare Earth Complexes Containing Piperonal Dimethyl Acetal and Dicyclopentadienyl - MEI, LUO; HUAI-ZHU, MA; QING-DE, SU; QIAN-RONG, LI (Asian Journal of Chemistry, 2010)
A number of rare earth complexes containing piperonal dimethyl acetal and dicyclopentadienyl can catalyze a series of methacrylate polymerization. From the results we can conclude that these kinds of complexes are highly active catalysts.